Hubungan Perilaku Merokok dengan Tekanan Darah Sistolik dan Tekanan Darah Diastolik pada Masyarakat di Kecamatan Kamanre Kabupaten Luwu Sulawesi Selatan: The Relationship of Smoking Behavior with Systolic Blood Pressure and Diastolic Blood Pressure in Communities in Kamanre Subdistrict of Luwu District of South Sulawesi - Arni Arni; Izal Zahran; Anugrah Umar (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Smoking behavior is a lifestyle that affects blood pressure in a person suffering from hypertension. Cigarettes contain nicotine which can make a person dependent by stimulating dopamine in the brain and increasing the hormone adrenaline which triggers the heart to work harder so that it has an impact on high blood pressure or hypertension in the sufferer. This study aims to identify the relationship between smoking behavior and systolic blood pressure and diastolic blood pressure in communities in Kamanre District, Luwu Regency, South Sulawesi. This research is a quantitative study that uses a correlation analytical research design with a cross-sectional approach. The sample in this study was 96 respondents. The sampling technique used is purposive sampling. The results of the study were analyzed using the chi-square test. Based on the chi-square test, there is a meaningful relationship between the number of cigarettes and blood pressure where (p value < 0.05) p = 0.016 for systolic blood pressure and p = 0.014 for diastolic blood pressure. The results of the chi-square test between cigarette type and blood pressure did not have a meaningful relationship p = 1,000 for systolic blood pressure and p = 0.294 for diastolic blood pressure. And the chi-square test results between smoking duration and systolic blood pressure there is a meaningful relationship p = 0.027 and diastolic blood pressure p = 1,000 there is no meaningful relationship.